2011
DOI: 10.1097/nmd.0b013e31822fcbfb
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Its Relationship to Dissociation in Patients With Panic Disorder

Abstract: Conditions that impede the regulation of emotional arousal, such as alexithymia and dissociation, may underlie panic attacks. This study aimed to evaluate the relationship between alexithymia and dissociation in patients with panic disorder (PD). We assessed 95 PD outpatients with regard to alexithymia (20-item Toronto Alexithymia Scale), dissociation (Dissociation Experience Scale), and overall psychological distress (Symptom Checklist 90-Revised, Global Severity Index). Regression analyses revealed a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Previous investigations have found a significant association of alexithymia with anxiety symptoms both in general [64] and in clinical [65] populations, particularly obsessive-compulsive disorder [66][67][68] and panic disorder [69,70]. It has been suggested that dissociation may be one of the leading mechanisms linking alexithymia to the experience of anxiety, reflecting the disintegration between emotion schemas and consciousness and, in particular, the transformation of stress-induced arousal into a generalized autonomic discharge [3,71] and affect dysregulation [72].…”
Section: Discussionmentioning
confidence: 98%
“…Previous investigations have found a significant association of alexithymia with anxiety symptoms both in general [64] and in clinical [65] populations, particularly obsessive-compulsive disorder [66][67][68] and panic disorder [69,70]. It has been suggested that dissociation may be one of the leading mechanisms linking alexithymia to the experience of anxiety, reflecting the disintegration between emotion schemas and consciousness and, in particular, the transformation of stress-induced arousal into a generalized autonomic discharge [3,71] and affect dysregulation [72].…”
Section: Discussionmentioning
confidence: 98%
“…Taken together, these findings support the hypothesis of a specific relationship between some anxiety and depressive symptoms and definite alexithymic dimensions. Indeed, previous studies [23,35,36] reported an association between psychic anxiety and DIF dimension. Further, DDF elevation has been associated with suicide ideation in depressed patients [37] as well as with depersonalization/derealization in PD patients [30] whereas the EOT dimension has been positively related to psychomotor retardation in major depressed patients [38].…”
Section: (N = 38)mentioning
confidence: 94%
“…However, in patients with high levels of alexithymia, the aims of psychotherapy should also include improvements in the awareness of feelings, thoughts and fantasies to facilitate the regulation of emotional arousal. Furthermore, an improved ability to regulate their emotions may help patients with dizziness to cope effectively with stressful events in their daily life [56]. Thus, it may be possible for alexithymic patients with dizziness to reduce their dizziness symptoms and to improve their HRQoL.…”
Section: Discussionmentioning
confidence: 99%